2014
DOI: 10.1073/pnas.1419156112
|View full text |Cite
|
Sign up to set email alerts
|

TORC1 regulators Iml1/GATOR1 and GATOR2 control meiotic entry and oocyte development in Drosophila

Abstract: In single-cell eukaryotes the pathways that monitor nutrient availability are central to initiating the meiotic program and gametogenesis. In Saccharomyces cerevisiae an essential step in the transition to the meiotic cycle is the down-regulation of the nutrient-sensitive target of rapamycin complex 1 (TORC1) by the increased minichromosome loss 1/ GTPase-activating proteins toward Rags 1 (Iml1/ GATOR1) complex in response to amino acid starvation. How metabolic inputs influence early meiotic progression and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
88
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(95 citation statements)
references
References 41 publications
6
88
1
Order By: Relevance
“…As case 1 had a smaller r (X) chromosome compared to case 2, we analysed the additional genes deleted and found that the extra region deleted in case 1 (Xq21.33-Xq22.1) were harbouring genes involved in thyroid hormone signalling, insulin receptor signalling, meiosis regulation, cell cycle regulation and chromatin organization. Alterations in these pathways are reported to be responsible for ovarian dysfunction [1,5,9,31,36,46].…”
Section: Discussionmentioning
confidence: 99%
“…As case 1 had a smaller r (X) chromosome compared to case 2, we analysed the additional genes deleted and found that the extra region deleted in case 1 (Xq21.33-Xq22.1) were harbouring genes involved in thyroid hormone signalling, insulin receptor signalling, meiosis regulation, cell cycle regulation and chromatin organization. Alterations in these pathways are reported to be responsible for ovarian dysfunction [1,5,9,31,36,46].…”
Section: Discussionmentioning
confidence: 99%
“…HS-FLP , UAS-RFP FRT19A/nprl2 1 FRT19A , HS-FLP ; Ubi-GFP FRT80B/nprl3 1 FRT80B and HS-FLP ; Ubi-GFP FRT80B/iml1 1 FRT80B flies were used to generate mutant clones in the germline and somatic cells of the ovary as previously reported (Wei et al 2014). Briefly, female flies were heat-shocked for 2 hr at 37° each day for 3 d. Subsequently, flies were cultured in standard media for an additional 2 d before dissection.…”
Section: Methodsmentioning
confidence: 99%
“…Western blots were performed as described previously (Wei et al 2014). Antibodies were used at the following concentrations: rabbit anti-P-S6K at 1:500 (Cell Signaling) and guinea pig anti-S6K at 1:10,000 (Hahn et al 2010).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, insulin signaling cell autonomously controls the growth of germline cysts and vitellogenesis (Hsu et al, 2008; LaFever and Drummond-Barbosa, 2005), and act through follicle cells to modulate the microtubule cytoskeleton and processing body formation in underlying germline cysts (Burn et al, 2015). The nutrient sensor Target of rapamycin (TOR) has multiple roles in the GSC and follicle stem cell lineages (LaFever et al, 2010; Sun et al, 2010), and its appropriate downregulation on a poor diet is important for survival of previtellogenic egg chambers (Wei et al, 2014). Ecdysone stimulates GSC responsiveness to niche signals, controls germline differentiation, and stimulates oocyte lipid accumulation (Ables et al, 2015; Ables and Drummond-Barbosa, 2010; Konig et al, 2011; Morris and Spradling, 2012; Sieber and Spradling, 2015).…”
Section: Introductionmentioning
confidence: 99%